The experience of implementing a social health insurance programme at health facilities in Khyber-Pakhtunkhwa, Pakistan - Shifa Salman Habib; Anum Shaikh; Kiran Sohail Azeemi; Waqas Hameed; Junaid Ur Rehman Siddiqui; Ali Hussaini; Asma Altaf Hussain Merchant; Adil Haider; Sameen Siddiqi (Journal of the Pakistan Medical Association, 2024)
Objective:To explore the experiences of key stakeholders, including hospital managers, clinicians, and hospital-based State Life Insurance Corporation (SLIC) representatives, SCP's implementation challenges and successes. Methods: A qualitative descriptive exploratory design was employed across 38 empanelled public and private facilities in KP. Key informant interviews (n=103) were conducted until data saturation was reached, exploring barriers and facilitators within the SCP's operational framework. Data were analyzed using NVivo software, applying a mix of deductive and inductive approaches. Results: Strengths and enablers included a comprehensive benefits package design, a robust third-party administrative system, and the digitization of health management information systems for efficiency. Implementation barriers included low reimbursement rates affecting service quality at health facilities, documentation issues hindering patient access, uneven availability of services causing patient frustration, resource-intensive claim preparation with a slow reimbursement process, and a lack of quality assurance mechanisms. Conclusion: This study provides a nuanced understanding of the SCP implementation, highlighting the need for revisiting reimbursement rates, addressing documentation challenges, ensuring service availability, streamlining reimbursement processes, and strengthening quality assurance mechanisms. The SCP's comprehensive benefits package, effective purchaser-provider relationships, and digitization efforts emerge as key strengths that contribute to its success. Keywords: Sehat Card Program (SCP), Social Health Insurance, Implementation Challenges. Stakeholder Perspectives, Reimbursement Processes, Khyber Pakhtunkhwa